Elementos epistemológicos substantivos do turismo como fenômeno social e humano - Maccoppi, Grazielle Ueno (2023)
Given the reality of the devaluation of sciences and humanities, it’s possible to identify a depreciation of the philosophical reflection in the production of scientific knowledge. Such depreciation is perceived in the field of tourism due to the theoretical and interpretative fragility that conditions its studies to reductionism and the maintenance of a disciplinary and deterministic approach. Tourism is defined as a complex social phenomenon that occurs in territorial relations. With the premise that philosophical reflection promotes critical and reflective study capable of generating renewal and updating of science, this work aims to contribute to an epistemological discussion in the field of tourism. Epistemology is understood as a form of applying knowledge, meaning it’s linked to the method of knowledge production and exposition (Faria, 2022). The overall goal is to unveil the substantive elements of tourism as a social and human phenomenon. The critical proposition of knowledge is adopted as a reference through the Ontology, Critical Epistemology of the Concrete, organized to address the scope of Humanities, Social, and Applied Social Sciences with an emphasis on Organizational Studies. Stemming from the constituent elements and gaps in tourism, the coloniality of scientific knowledge and the hegemonic structure present in the epistemological foundations composing the phenomenon are identified. As a structure in pursuit of greater independence, a discussion emerges about the influence of technoscience and scientific autonomy in the field. In this context, substantive elements of the phenomenon emerge, capable of forming a more inclusive and diverse epistemological approach to tourism.